PEMBUBARAN PARTAI POLITIK TERLIBAT KORUPSI OLEH MAHKAMAH KONSTITUSI - Suhariyanto, Didik (JURNAL KONSTITUSI, 2011)
If the political parties and board, a member of its cadres in a structured, systematic and massive corruption, it can be dissolved by the Constitutional Court. Legal action for the dissolution of political parties must be a consequence of judicial findings of violations of constitutional or based on legal facts. Dissolution a political party is the legal expiration of the existence of political parties. All forms of corruption have the effect of the destruction of the political culture, political institutions, and public trust in the leadership and government